2009
DOI: 10.1211/jpp.61.06.0007
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, physicochemical characterization and biological evaluation of cefodizime metal ion complexes

Abstract: The antibacterial activity of cefodizime was not affected by complexation with Al3+ but it was reduced by complexation with the other tested metal ions against the bacteria under study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The solubility of Ceftiofur hydrochloride changed drastically on its complexation with the metal ions under study which is in consonance with the results reported earlier for the complexes of other cephalosporins. 22 In conformity with the result of cefpodizime, 22 there was no significant change in the UV spectra of metal complexes from Ceftiofur hydrochloride. In case of IR spectrum it is found that compared to the characteristic band at 1764 cm -1 and 1606 cm -1 in case of Ceftiofur hydrochloride corresponding to the stretching frequency of the -lactam carbonyl (CO) group and the amidic carbonyl group, respectively, in metal complexes they appeared in the range of 1743-1777 cm -1 and 1635-1667 cm -1 ,respectively.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The solubility of Ceftiofur hydrochloride changed drastically on its complexation with the metal ions under study which is in consonance with the results reported earlier for the complexes of other cephalosporins. 22 In conformity with the result of cefpodizime, 22 there was no significant change in the UV spectra of metal complexes from Ceftiofur hydrochloride. In case of IR spectrum it is found that compared to the characteristic band at 1764 cm -1 and 1606 cm -1 in case of Ceftiofur hydrochloride corresponding to the stretching frequency of the -lactam carbonyl (CO) group and the amidic carbonyl group, respectively, in metal complexes they appeared in the range of 1743-1777 cm -1 and 1635-1667 cm -1 ,respectively.…”
Section: Resultssupporting
confidence: 52%
“…9 The cephalosporin metal complexes have been analyzed by various spectral, thermal voltammetric and by HPLC methods. [10][11][12][13] A large number of reports on the effect of chelation on the biological activity of cephalosporin antibiotics [14][15][16][17][18][19][20][21][22] have appeared in the literature. In several cases, the results were found to be encouraging while in other cases, the activity was only comparable or somewhat lower.…”
Section: Introductionmentioning
confidence: 99%
“…Some cephalosporin antibiotics are known to form tight complexes with divalent metal ions, 27 including Zn 2+ , which suggested that the inhibition might result from an E-Zn 2+ –Ceph C enzyme-metal-bridged complex. However, further investigation showed that Zn 2+ alone (as the chloride salt) was also inhibitory (IC 50 Zn = 2.1 ± 0.2 μM, h = 1.2 ± 0.1; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The metal ion contents were determined by complexmetric titration procedures and atomic absorption spectroscopy. The halogen content was determined by titration with standard Hg (NO 3 ) 2 solution using diphenylcarbazone indicator [24][25][26][27][28][29][30]. The analytical data and physical properties of the studied compounds are represented in Table 1 as previously reported [10][11].…”
Section: Synthesis Of Simple and Mixed Metallocephradines And Metallomentioning
confidence: 99%